Inclusive Culture Management at Islamic Elementary Schools: The Ideal Concept - Minsih, Minsih; Hidayat, Muhamad Taufik (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to find the ideal concept in creating an excellent inclusive culture in implementing inclusive education. The method used was qualitative with phenomenological design. Collecting data through interviews, participant observation, documentation, and focus group discussions (FGDs). The data analysis technique used was Cresswell's theory which states that: reduction, data display, and concluding. The study results show five development steps: First, the cultivation of values in the school environment starts from the classroom using a balanced collaboration between the verbal explanation of the material and its application in daily life. Second, habituation of behavior patterns that are carried out to deal with cases encountered in the field requires them to solve them. Third, an intervention or an action taken in the form of treatment of students' emotional problems. Fourth, exemplary for all school members and residents at home. Fifth, a persuasive approach or subtly inviting school members to create an inclusive culture through parenting activities, capacity building, workshops, and FGDs